Study on Antimicrobial Effects of Phytotherapy in the Treatment of Children with Pyelonephritis - Natal'ya I. Averyanova; Nadezhda Yu. Kolomeets; Vladislava V. Kozlova; Tat'yana I. Rudavina (Union of pediatricians of Russia, 2017)
Background. Improvement of treatment methods and relapse prevention of pyelonephritis in children is relevant to pediatrics. The study of the antibacterial possibilities of herbal medicines (HM) provoke great interest for researches . The aim of the survey was to investigate the antimicrobial properties of combined phytotherapy in vitro. Methods. Two microbiological researches were performed in vitro. One of them was conducted using the microtechnique for serial dilution-antibiotic sensitivity testing of 62 cultures (genera Escherichia, Klebsiella, Proteus and Pseudomonas, Staphylococcus, Streptococcus) isolated in significantly diagnostic concentration from the urine of children in the acute phase of pyelonephritis. The antibacterial effect of RLP was detected using the microtechnique for serial dilution. To exclude the antibacterial effect of the alcohol present in the phytopreparations, a number of analogous dilutions were placed in 19.5% solution of ethyl alcohol. At the same time, the sterility of the reaction components was monitored. The second research studied the concentration changes of the microbial suspension of Escherichia coli isolated from the urine of children before the treatment onset with incubation of different concentrations of phytopreparations and at a different exposure periods. Results. Studies on the antimicrobial activity of HM in vitro demonstrated the antimicrobial effect of HM on 58% of the examined cultures. The highest drug sensitivity was revealed in the genera Klebsiella (80%), Staphylococcus (77%), and E. coli (51.5%). Studies on the concentration changes of microbial suspension of E. coli detected 100% activity of undiluted HM at a 24-hour exposure period (sample D). A significant decrease in the pathogen growth was also obtained with HM with the dilution ratio 1:1 at a 24-hour exposure period. Conclusion. The microbiological analyses demonstrated and confirmed the antibacterial characteristics of HM.